Enteric pathogens through life stages - Kolling, Glynis; Wu, Martin; Guerrant, Richard L. (Frontiers in Cellular and Infection Microbiology, 2012)
Enteric infections and diarrheal diseases constitute pervasive health burdens throughout the world, with rates being highest at the two ends of life. During the first 2–3 years of life, much of the disease burden may be attributed to infection with enteric pathogens including Salmonella, rotavirus, and many other bacterial, viral, and protozoan organisms; however, infections due to Clostridium difficile exhibit steady increases with age. Still others, like Campylobacter infections in industrialized settings are high in early life (<2 years old) and increase again in early adulthood (called the “second weaning” by some). The reasons for these differences undoubtedly reside in part in pathogen differences; however, host factors including the commensal intestinal microbial communities, immune responses (innate and acquired), and age-dependant shifts likely play important roles. Interplay of these factors is illustrated by studies examining changes in human gut microbiota with inflammatory bowel disease and irritable bowel syndrome. Recent gut microbial surveys have indicated dramatic shifts in gut microbial population structure from infants to young adults to the elders. An understanding of the evolution of these factors and their interactions (e.g., how does gut microbiota modulate the “inflamm-aging” process or vice versa) through the human life “cycle” will be important in better addressing and controlling these enteric infections and their consequences for both quality and quantity of life (often assessed as disability adjusted life-years or “DALYs”).